A consciência política na teoria da justiça de Joaquim Carlos Salgado - Renon Pessoa Fonseca (2018)
This thesis proposes an interpretation for the moment of political consciousness in Joaquim Carlos Salgado's Theory of Justice, in which it is presented as the mediation between the individual moral conscience and the universal juridical consciousness. For this, we use Hegels and Lima Vazs philosophies, that influenced decisively the thought of Salgado, in order to establish in the concept of recognition, present in both, the universalizing role played by political consciousness. As a background of this main objective, we also try to show that from Salgado's reflection emerges an ethical system in which law occupies the culmination point, as the maximum ethical of a culture.